Tubulin Nanorings. Issue 8 (2016) - Boukari, Hacène; Sackett, Dan L.
ABSTRACT: Biological systems routinely produce nanoscopic molecular structures with considerably less dispersion in size and shape than encountered in most manufactured materials. Indeed, Biological structures are frequently and essentially monodisperse. An example of this uniformity, combined with an intriguing geometry, is the nanometer-scale protein nanorings produced by interaction of the protein tubulin with certain hydrophobic tri-, tetra- and pentapeptides originally extracted as natural products from marine biosystems. Different peptides produce different sized nanorings, but we focus on those produced by binding to tubulin of the cyclic depsipeptide cryptophycin. The nanorings that form upon binding of this ligand show a sharp mass distribution indicating that the nanorings are made of 8 tubulin dimers of 100 kDa. In this submission, we demonstrate how a combination of fluorescence correlation spectroscopy, dynamic light scattering, electron microscopy, analytical ultracentrifugation, small-angle neutron scattering, and modeling is applied to reveal interactions of tubulin and cryptophycin in solution and to characterize their structures. We find that the cryptophycin-tubulin nanorings (∼25 nm diameter) are single-walled, appear rigid, are composed of 8 tubulin dimers in a single closed ring, and are stable upon dilution to nanomolar concentrations. Similar studies with a different peptide, the linear pentapeptide dolastatin 10, demonstrated that binding of this peptide to tubulin produces larger nanorings (14 tubulin dimers, ∼45 nm diameter rings), with slightly different properties. The ability to adjust the ring size with different peptides, and produce uniform nanorings with properties that differ slightly between size classes, makes the tubulin-peptide ring structures an appealing structural system.